Central banks and information provided to the private sector - Giovanni Di Bartolomeo; Enrico Marchetti (PSL Quarterly Review, 2012)
This paper examines the information provided to the private sector by central banks. By using the principal component analysis, we investigated the variance of the procedural rules followed by nine major central banks about informationtreatments. We investigate problems related to the information coming from the central banks by focusing on the quantity and quality perspectives and highlight the methodological complexity of the investigation. We find that a synthetic quantitative index of transparency is not enough to represent the phenomenon since it can result misleading in understanding the behavior of institutionally different central banks associated with the same index values.